1996
DOI: 10.1056/nejm199608153350702
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison of Multimodal Therapy and Surgery for Esophageal Adenocarcinoma

Abstract: Background Uncontrolled studies suggest that a combination of chemotherapy and radiotherapy improves the survival of patients with esophageal adenocarcinoma. We conducted a prospective, randomized trial comparing surgery alone with combined chemotherapy, radiotherapy, and surgery. Methods Patients assigned to multimodal therapy received two courses of chemotherapy in weeks 1 and 6 (fluorouracil, 15 mg per kilogram of body weight daily for five days, and cisplatin, 75 mg per square meter of body-surface area on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
1,041
7
46

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,810 publications
(1,139 citation statements)
references
References 27 publications
32
1,041
7
46
Order By: Relevance
“…Twelve patients (median age 64 years; 67% male, 58% moderately differentiated, 83% esophageal, 100% HER2‐positive) received a median of 5.6 weeks of treatment (range: 1.1–8.4). Four patients underwent tumor resection and one of the four patients (25%) had a pCR, which was similar to the pCR rates of previously reported studies [1], [2], [3]. However, the number of patients evaluated in the present study was too low to make an accurate comparison with other studies.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Twelve patients (median age 64 years; 67% male, 58% moderately differentiated, 83% esophageal, 100% HER2‐positive) received a median of 5.6 weeks of treatment (range: 1.1–8.4). Four patients underwent tumor resection and one of the four patients (25%) had a pCR, which was similar to the pCR rates of previously reported studies [1], [2], [3]. However, the number of patients evaluated in the present study was too low to make an accurate comparison with other studies.…”
supporting
confidence: 88%
“…Neoadjuvant chemoradiation therapy for patients with localized esophagogastric cancers has been the subject of much discussion and controversy, with conflicting results compared with surgery alone seen in previous randomized clinical trials [1], [2], [3]. Pathologic complete response (pCR) rates after neoadjuvant chemoradiation therapy are in the 25% range [1], [2], [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4 Several authors have investigated the beneficial role of neoadjuvant chemoradiation therapy (CRT) in patients with potentially resectable esophageal adenocarcinoma to improve long-term survival. 5,6 Local preoperative staging of esophageal carcinoma with EUS is important in selecting better candidates for surgery and in determining which patients have potentially resectable disease. Studies have continued to support the utility of EUS in the initial staging of esophageal carcinoma.…”
mentioning
confidence: 99%
“…Subset analyses demonstrate that only true complete responders have a durable diseasefree and overall survival benefit. [26][27][28][29] The addition of gene therapy to currently employed modalities of chemotherapy, radiotherapy and surgery attempts to enhance the overall antitumor efficacy and increase the number of complete responders. It has been reported that MUC1 is expressed in as high as 43% of esophageal adenocarcinoma specimens and that a majority of these specimens were poorly differentiated advanced neoplasms.…”
Section: Discussionmentioning
confidence: 99%